Web 2.0 and libraries : impacts, technologies and trends - Parkes, David; Walton, Geoff (Chandos information professional series., 2010)
In a world where computing power, ubiquity and connectivity create powerful new ways to facilitate learning, this book examines how librarians and information professionals can utilize emerging technologies to expand service and resource delivery. With contributions from leading professionals, including lecturers, librarians and e-learning technologists, this bookl explores strategic approaches for effectively implementing, living with, and managing revolutionary technological change in libraries. Explores the impact of the social and technological aspects of Web 2.0 on libraries and library servicesDraws on empirical researchExperienced practitioners.